The Impact Of Creativity And PKWU Learning Achievement On Entrepreneurial Interest Among High School Students: A Case Study Of SMA Negeri 6 Depok - sadiyah, allimatus (Jurnal Edukasi, 2025)
This study explores the influence of creativity and academic performance in the Prakarya dan Kewirausahaan (PKWU) subject on entrepreneurial interest among high school students at SMA Negeri 6 Depok. As entrepreneurship education becomes increasingly critical in addressing youth unemployment, understanding the factors that drive students' entrepreneurial aspirations is vital. The research uses a quantitative approach, employing Structural Equation Modeling (SEM) to analyze data from 200 grade 12 students. Results reveal that both creativity and PKWU learning achievement positively and significantly affect entrepreneurial interest, with PKWU learning achievement having a stronger impact. These findings suggest that while creativity fosters innovative thinking, the practical skills provided through PKWU have a more direct influence on students' entrepreneurial ambitions. The study concludes by emphasizing the importance of integrating practical entrepreneurial experiences and creativity in educational curricula to cultivate a well-rounded entrepreneurial mindset. Limitations and future research directions, including expanding the sample size and using a longitudinal design, are discussed. Keywords: Creativity; entrepreneurial interest; entrepreneurship education; pkwu; structural equation modeling.